Pelatihan Make-Up Karnaval Bagi Siswa SMA Labschool Unesa 1 - Ika Anggun Camelia; Kartika Herlina Candraning Shiam; Pungki Siregar; Aqim Amral Hukmi; Djuli Djatiprambudi (Jurnal Dremi (Demi Pengabdi Masyarakat), 2025)
Carnival art activities in schools are often constrained by students' lack of skills in makeup and supporting accessory creation. This training aimed to improve the ability of students from SMA Labschool Unesa 1 in carnival makeup and independent headpiece making. The methods used included lecture, demonstration, Q&A, and paired simulation with the Bird of Paradisetheme. The results showed that all participants divided into 10 teams successfully created headpieces and applied creative, on-theme character makeup within 3 hours. Participants became more skilled, confident, and able to collaborate effectively. The long-term impact of this activity is reducing the school's dependence on external makeup artists, optimizing the budget, and fostering a culture of creativity and self-reliance among students. This training proves that a project-based practical approach is effective in developing life skills and art literacy among high school students.